Does supermarket purchase affect the dietary practices of households?: Some empirical evidence from Guatemala - Asfaw, Abay (Wiley, 2008)
Very little is known about how changes in the retail environment affect consumers’diet and health status, especially in developing countries. This article examines the impact of supermarket purchases on the dietary practices of households in Guatemala, using an instrumental variable method to take account of the potential endogeneity of the supermarket purchase variable. The results reveal that supermarket purchases increase the share of highly and partially processed foods at the expense of staple foods, and are also positively and significantly associated with individual Body Mass Index. Different policy moves should be envisaged towards‘healthier’diets.